2016
DOI: 10.1021/acs.iecr.6b03117
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite ZSM5-Filled PVDF Hollow Fiber Mixed Matrix Membranes for Efficient Carbon Dioxide Removal via Membrane Contactor

Abstract: ZSM5 zeolite-filled PVDF mixed matrix membranes (MMMs) were wet spun and used for CO2 absorption in a contactor system. The properties of ZSM5 were analytically characterized. SEM images revealed the fully asymmetric structure of membranes, in which the creation of finger-like macrovoids was promoted with increasing filler loading. A significant increase in gas permeance was observed, which was associated with the porosity increase of the membrane surface despite the decrease in surface pore size. The surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…3D nanomaterials with rigid cage-like structure offer some structural advantages that are important for a gas-separation nanocomposite membrane. The last decade has witnessed tremendous efforts in developing MMM gas separation membranes based on 3D zeolite [ 102 , 103 , 104 ], MOF [ 105 , 106 , 107 ] and POSS [ 108 , 109 , 110 ]. In particular, MOFs exhibit a strong affinity towards CO 2 molecules and are able to enhance CO 2 solubility in the membrane hence offering excellent CO 2 separation performance [ 111 , 112 ].…”
Section: Tailoring the Dimensions Of Nanostructures To The Separatmentioning
confidence: 99%
“…3D nanomaterials with rigid cage-like structure offer some structural advantages that are important for a gas-separation nanocomposite membrane. The last decade has witnessed tremendous efforts in developing MMM gas separation membranes based on 3D zeolite [ 102 , 103 , 104 ], MOF [ 105 , 106 , 107 ] and POSS [ 108 , 109 , 110 ]. In particular, MOFs exhibit a strong affinity towards CO 2 molecules and are able to enhance CO 2 solubility in the membrane hence offering excellent CO 2 separation performance [ 111 , 112 ].…”
Section: Tailoring the Dimensions Of Nanostructures To The Separatmentioning
confidence: 99%
“…It has been shown that the CO 2 flux remained stable for 31 days of continuous operation owing to the hydrophobicity rendered by fSiO 2 particles . Besides the utilization of fSiO 2 , ,, other inorganic materials, such as CaCO 3 , cloisite, , montmorillonite (MMT), , zeolite (ZSM-5), and TiO 2 , have also been explored to fabricate inorganic–organic hybrid membranes for applications in membrane contactors.…”
Section: Co2 Absorption Using Membrane Contactorsmentioning
confidence: 99%
“…The massive emissions of sulfur dioxide (SO 2 ) have adverse influences on the ecological environment and human health. In past decades, numerous researches have been focused on the absorption of SO 2 gas by employing gas–liquid membrane contactor technology, which displays the green and efficient industrial application prospect, avoiding the flooding, bubbling, gas–liquid entrainment problems. The investigation of acidic gas capture by membrane contactor can be classified into various categories: membrane design, , transfer mechanism, , absorption liquid, optimized operating process, , process simulation, etc. , To obtain the excellent acid gas absorption flux, a membrane contactor designed with a hydrophobic property is essential to keep absorbent liquid from immersing into the pores of membrane contactors. Therefore, a hydrophobic membrane material, such as polytetrafluoroethylene (PTFE), polypropylene (PP), has been used to prepare porous membrane contactors for desulfurization. …”
Section: Introductionmentioning
confidence: 99%
“…Polyvinylidene fluoride (PVDF) as a polymer matrix can be fabricated by the simple non-solvent-induced phase separation (NIPS) strategy, and pore sizes, distributions of pore size, and porosities are precisely tuned by membrane forming processes. ,, The performances can be evaluated by incorporating various particles. Zhang et.al prepared 4A@Cu as fillers and incorporated them into the PVDF matrix for fabrication of membrane contactors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation